Performance of RIS-Secured Short-Packet NOMA Systems With Discrete Phase-Shifter to Protect Digital Content and Copyright Against Untrusted User - Nguyen Quang Sang; Hye-Young Kim; Tan N. Nguyen; Minh Bui Vu; Phuong T. Tran; Tran Trung Duy; Byung-Seo Kim; Miroslav Voznak (IEEE Access)
Future wireless communications are expected to serve a wide range of emerging applications, such as Online Gaming, Extended Reality (XR), Metaverses, Healthcare or Telemetry, where communication from diverse connected Internet of Things (IoT) devices require not only stringent conditions such as ultra-reliability and low-latency communication (URLLC) together with high bandwidth but also concerns about content security as well as copyright protection. To deal with URLLC demands, Short-Packet Communication (SPC) has been recently considered a vital solution. Meanwhile, to meet high spectrum utilization, Non-Orthogonal Multiple Access (NOMA) has emerged as a potential technology in the last decade, for its ability to serve multi-user communication simultaneously by exploiting power-domain rather than time or frequency domains. Especially, incorporating Reconfigurable Intelligent Surfaces (RIS) with NOMA/SPC-based systems can further boost the system’s spectral efficiency as well as enhance communication coverage. However, NOMA-based systems hugely demand a reliable user-paring process, which imposes challenges in ensuring secure short-packet delivery for emerging IoT applications. Hence, this paper studies downlink RIS-assisted short-packet NOMA systems with the focus of improving the secure performance of the pairing process with untrusted users. Our primary innovation lies in developing an arbitrary user-pairing strategy for NOMA-based systems to secure short-packet delivery for IoT applications by jointly designing the power allocation policy and RIS’s phase shifter. In this strategy, untrustworthy users will be allocated higher power levels than trustworthy users, while the latter will be configured with sub-optimal phase shift criteria at RIS to maximize its cascaded channel gain. On this foundation, we derive closed-form expressions for the average block-error rate (BLER) to analyze the performance of trustworthy users as well as the average secure BLER to quantify the secure performance when untrustworthy users wiretap trustworthy users’ information using successive interference mechanisms. Moreover, we further develop asymptotic expressions for both cases to measure the diversity gain and induce key parameters. Subsequently, Monte Carlo simulations are provided as a benchmark to corroborate the theoretical findings. This demonstrates that our work can offer a groundbreaking solution for secure and efficient wireless communication, which can also be applied to digital content protection, such as gaming.